2009
DOI: 10.1183/09031936.00185808
|View full text |Cite|
|
Sign up to set email alerts
|

No evidence for interstitial lung oedema by extensive pulmonary function testing at 4,559 m

Abstract: The aim of the present study was to better understand previously reported changes in lung function at high altitude.Comprehensive pulmonary function testing utilising body plethysmography and assessment of changes in closing volume were carried out at sea level and repeatedly over 2 days at high altitude (4,559 m) in 34 mountaineers.In subjects without high-altitude pulmonary oedema (HAPE), there was no significant difference in total lung capacity, forced vital capacity, closing volume and lung compliance bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 43 publications
5
49
1
Order By: Relevance
“…However, there is a large overlap of individual values [7] and statistically significant differences can only be obtained in studies of large groups. These blood gas changes might be due to a mild interstitial oedema not visible on chest radiographs [8], but suggested by a slight decrease of vital capacity and increase of closing volume [9,10]; however, these are inconsistent findings [11]. Furthermore, a lower ventilatory drive in hypoxia might contribute to more severe hypoxaemia in AMS, at least in some individuals [12,13].…”
Section: Ams and Hacementioning
confidence: 99%
“…However, there is a large overlap of individual values [7] and statistically significant differences can only be obtained in studies of large groups. These blood gas changes might be due to a mild interstitial oedema not visible on chest radiographs [8], but suggested by a slight decrease of vital capacity and increase of closing volume [9,10]; however, these are inconsistent findings [11]. Furthermore, a lower ventilatory drive in hypoxia might contribute to more severe hypoxaemia in AMS, at least in some individuals [12,13].…”
Section: Ams and Hacementioning
confidence: 99%
“…Hypoxia induces pulmonary vasoconstriction, an adaption that reduces ventilation-perfusion mismatch and optimizes the lung diffusion and perfusion matching (8,36). But exercise in the hypoxic environment is associated with a deterioration of ventilation-perfusion matching, which is only partly corrected by hypoxic vasoconstriction (36).…”
Section: Introductionmentioning
confidence: 99%
“…Guénard points out a discrepancy of the transfer factor of the lung for carbon monoxide (TL,CO) measurements between data published in his group's abstract [1] and data we reported recently [2]. DE BISSCHOP et al [1] observed a small but significant decrease in TL,CO in acclimatised subjects after maximal exercise at 5,000 m, which H. Guénard considers to be in disagreement with the small increase we found in nonacclimatised subjects at rest at 4,559 m. He suggests that the discrepancy is due to an erroneous calculation of diffusing capacity of the lung for carbon monoxide (DL,CO) on our part.…”
Section: From the Authorsmentioning
confidence: 97%
“…Guénard points out a discrepancy of the transfer factor of the lung for carbon monoxide (TL,CO) measurements between data published in his group's abstract [1] and data we reported recently [2]. DE BISSCHOP et al [1] observed a small but significant decrease in TL,CO in acclimatised subjects after maximal exercise at 5,000 m, which H. Guénard considers to be in disagreement with the small increase we found in nonacclimatised subjects at rest at 4,559 m. He suggests that the discrepancy is due to an erroneous calculation of diffusing capacity of the lung for carbon monoxide (DL,CO) on our part. Furthermore, he points out that transfer factor of the lung for nitric oxide (TL,NO), which was also slightly decreased in the study of DE BISSCHOP et al [1], is a better measure of diffusion than TL,CO, since nitric oxide uptake is dependent only on membrane conductance and is not influenced by blood conductance.…”
Section: From the Authorsmentioning
confidence: 97%